Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1365-2966.2005.09219.x
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz instability and circulation transfer at an isotropic-anisotropic superfluid interface in a neutron star

Abstract: A recent laboratory experiment suggests that a Kelvin–Helmholtz (KH) instability at the interface between two superfluids – one rotating and anisotropic, the other stationary and isotropic – may trigger sudden spin‐up of the stationary superfluid. This result suggests that a KH instability at the crust–core (1 S0–3 P2–superfluid) boundary of a neutron star may provide a trigger mechanism for pulsar glitches. We calculate the dispersion relation of the KH instability involving two different superfluids includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 36 publications
(129 reference statements)
3
58
0
Order By: Relevance
“…When the relative velocity between the two phases exceeds a critical value, the penetration of quantized vortices across the interface was detected by counting the number of vortices by NMR before and after the instability 1 . The Kelvin-Helmholtz instability in superfluid systems has been discussed on different kinds of interfaces, such as normal-superfluid interfaces [110,160], nuclear-nuclear superfluid interfaces [161], and superfluid-superfluid inter-face in atomic two-component BECs [162].…”
Section: Hydrodynamic Instabilities In Superfluid Systemsmentioning
confidence: 99%
“…When the relative velocity between the two phases exceeds a critical value, the penetration of quantized vortices across the interface was detected by counting the number of vortices by NMR before and after the instability 1 . The Kelvin-Helmholtz instability in superfluid systems has been discussed on different kinds of interfaces, such as normal-superfluid interfaces [110,160], nuclear-nuclear superfluid interfaces [161], and superfluid-superfluid inter-face in atomic two-component BECs [162].…”
Section: Hydrodynamic Instabilities In Superfluid Systemsmentioning
confidence: 99%
“…Mastrano and Melatos [181] suggested that a Kelvin-Helmholtz instability at the interface between the 1 S 0 and 3 P 2 superfluids in the star may trigger the glitch, complementing the bulk two-stream instability discussed above.…”
Section: Hydrodynamical Instabilitesmentioning
confidence: 99%
“…Here, for simplicity, we assume that the isotropic 1 S 0 phase fills the entire outer core. The 3 P 2 phase is anisotropic: gradients in the orientation (texture) of the pair angular momenta drive counterflows between the viscous and inviscid components of the superfluid (Vollhard & Wölfle 2002;Mastrano & Melatos 2005), introducing complications (e.g., boundary conditions at the 1 S 0 -3 P 2 interface) that lie outside the scope of this paper. 4 The outer core contains charged species, particularly protons and electrons, which are incorporated into the viscous component of the superfluid in our simulations.…”
Section: Idealized Hydrodynamic Model Of the Outer Core Of A Neutron mentioning
confidence: 99%